Skin Burn at the Site of Indifferent Electrode after Radiofrequency Catheter Ablation of AV Node for Atrial Fibrillation - Vanga, Subba Reddy (J Atr Fibrillation, 2008)
Radiofrequency Ablation of AV node with permanent pacemaker has been used to achieve rate control in persistent symptomatic atrial fibrillation. Although RF Ablation is safe, complications may occur in up to 3% of the procedures. A rare complication of 2nd degree skin burn at indifferent electrode site has been described here. This report highlights the rare but possible complication in patients undergoing such a procedure and help in preventing by taking appropriate measures.